Business Reports in English - Comfort Jeremy; Revell Rod; Stott Chris (Cambridge University Press, 1993)
This book is for Professionals or trainee Professionals in a wide range of fields in business, commerce, and administration who have to read and write reports in English. Acknowledgements, Overview, Collecting the Information, Using Graphs and Statistics, Selecting and Organizing the Material, Presenting Findings, Concluding and Recommending, Summarizing, Key, Glossary.